2022
DOI: 10.3390/foods11182895
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Evaluation of Interfacial Properties of Pea Protein Isolate–EGCG Molecular Complexes

Abstract: There is increasing interest in using plant-derived proteins in foods and beverages for environmental, health, and ethical reasons. However, the inherent physicochemical properties and functional performance of many plant proteins limit their widespread application. Here, we prepared pea protein isolate (PPI) dispersions using a combined pH-shift/heat treatment method, and then, prepared PPI-epigallocatechin-3-gallate (EGCG) complexes under neutral conditions. Spectroscopy, calorimetry, molecular docking, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…S3 illustrates the UV–vis absorption spectra of RP mixed with CUR/QUE/RES at various concentrations. The protein exhibited a prominent absorption peak at around 275 nm, attributed to the electronic transitions between π-type molecular orbitals occurs to aromatic rings of aromatic amino acids, as the local environment of tryptophan and tyrosine residues was highly sensitive to this wavelength ( Han et al, 2022 ). As the concentration of CUR/QUE/RES increased, the absorbance of the mixture gradually rose, indicating potential interactions between protein and polyphenols.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S3 illustrates the UV–vis absorption spectra of RP mixed with CUR/QUE/RES at various concentrations. The protein exhibited a prominent absorption peak at around 275 nm, attributed to the electronic transitions between π-type molecular orbitals occurs to aromatic rings of aromatic amino acids, as the local environment of tryptophan and tyrosine residues was highly sensitive to this wavelength ( Han et al, 2022 ). As the concentration of CUR/QUE/RES increased, the absorbance of the mixture gradually rose, indicating potential interactions between protein and polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…The interactions can be used to fabricate polyphenol carriers, improving their stability and bioavailability ( Chen et al, 2023 , Jiang et al, 2023 ). Additionally, the interaction can be applied to alter functional properties of proteins, such as emulsifying and foaming capacity ( Han et al, 2022 , Pan et al, 2022 ). Polyphenols interact with protein through various mechanisms such as hydrogen bonding, electrostatic interactions, and hydrophobic interactions, leading to changes in the spatial conformation of protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-covalent dynamic bonds form through intermolecular forces or interactions with substances, such as protein–protein, protein–polysaccharide, and protein–polyphenol interactions, resulting in protein conformation changes as well as the formation of protein complexation [ 92 , 93 , 94 ]. Current research highlights the potential of combining pulse proteins with other edible components, such as polymers or small molecules, in order to construct multicomponent molecular complexes, thus improving the quality and nutritional value of food products [ 92 , 94 , 95 , 96 ].…”
Section: Modification Strategies Of Pulse Protein Isolatesmentioning
confidence: 99%
“…Furthermore, the high contents of lysine and branched chain amino acids and overall well-balanced amino acid profile make pea protein a suitable substitute for animal proteins . PPI and its derived hydrolysates and peptides also possess many health-related biological activities, including antioxidant, antihypertensive, cholesterol modulating, antidiabetic, and anti-inflammatory activities. PPI and its protein fractions, globulin, glutelin, and albumin, have been reported to form complexes with several polyphenols, leading to enhanced functional properties. Our previous studies have demonstrated the effects of PPI, its fractions, and succinylated form on curcumin binding, encapsulation efficiency, and release profiles. , However, information about the effect of PPI–curcumin complexation on protein digestibility is lacking. Therefore, the purpose of this study was to characterize the interaction, microstructure, and in vitro protein digestibility of PPI in the presence of different curcumin concentrations to better understand the role of protein–polyphenol complexation on nutritional quality.…”
Section: Introductionmentioning
confidence: 99%